PENGARUH SERVANT LEADERSHIP, KARAKTERISTIK INDIVIDU, BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA APARATUR SIPIL NEGARA PADA PEMERINTAH PROVINSI SULAWESI BARAT - Muhammad Nadir (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2016)
This study aimed to analyze the influence of Servant Leadership, Individual Characteristics and Organizational Culture and Organizational Commitment and Employee Of State Civil Apparatus in West Celebes Provincial Government.The population in this study is the whole apparatus of Civil State (ASN) Government of West Sulawesi province, as many as 2,970 ASN, while samples were taken based on the Slovin’s formul, data was gathered throught distributed the questionnaires as much as 327 to the respondents which were the employees of ASN in the province of West Sulawesi but after a collected the quessionaire the researcher only able to collect about 262 copies and only 253 that can be analyzed, and the other does not allow for further analysis. Data was collected using survey method and analyzed by Likert scale with alternative answers ranging from not agree to Strongly Agree, while the data analized by Structural Equation Modelling version 19. The results of this studies indicate that the Servant Leadership, individual characteristics and organizational culture, organizational commitment in the province of West Sulaweesi get ratings in the high category, while the performance of civilian State Apparaturs is ini Very High category. While the test results prove the hypothesis that: Servant Leadership, individual characteristics and organizational culture significantly influence organizational commitment; Servant Leadership, individual characteristics and organizational culture have a significant effect on performance; and Organizational Commitment significant effect on performance. Thus the results of this study prove that all of the stated hypothesis were accepted.